Studi Prosedur Asesment Bahasa Arab di Mi Nurul Huda dan Implikasinya bagi Peningkatan Kualitas Pembelajaran - Tsani, Muhammad Jaohar; Arsyad, Hairuddin; Syihabuddin, Syihabuddin (CV. Creative Tugu Pena, 2024)
This study aims to analyze the quality of Arabic language learning evaluation focusing on the difficulty level of questions, discriminant power, and distractor function. The objectives are to enhance understanding of the importance of evaluation in learning, provide feedback to schools and teachers, and improve the learning process. The research method employs both qualitative and quantitative approaches, with the research subjects being school principals, Arabic language teachers, and fifth-grade students of MI Nurul Huda. Data are collected through observation, interviews, and documentation, then analyzed using Thematic Analysis for qualitative data and Descriptive Statistical Analysis for quantitative data. The findings indicate a lack of assessment question formulation policies, with questions tending to be moderately easy with good discriminant power. However, some distractors are not functioning optimally, indicating the need for improvement in assessment question formulation. This will help enhance learning effectiveness and academic achievement in the future. Keywords: Question Difficulty, Discriminant Power, Distractor Function